Hybrid DFT of electronic and vibrational properties of irondoped Β-GA2O3 crystals - Usseinov, A.; Koishybayeva, Zh.; Akilbekov, A. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2023)
This paper presents the results of calculations of energy and electron-optical properties of iron-doped β-Ga2O3. By analyzing the arrangement of the electronic levels of the impurity in the band gap for different charge states, it is shown that Fe is an acceptor impurity. Evaluation of both optical and thermodynamic transition levels indicates the deep nature of the iron acceptor impurity. In addition, iron can play the role of a donor at very low Fermi energies, but the probability of forming such a state is extremely low. We find that iron modifies Raman scattering in an ambiguous manner. Due to the low effective atomic mass of the substituted iron atom, doping leads to a pronounced enhancement of phonon modes of vibrations in the high-frequency range ( 600÷800 cm-1). The results obtained are in good agreement with experimental observations, confirming the acceptor character of the iron impurity.